Mechanism of AZDEGDN accelerating the decomposition of nitrocellulose: insights from reactive molecular simulations - Zhang, Ting; Qin, Weihua; Meng, Weifeng; Guo, Zhuiyue; Geng, Shuang; Cao, Weiguo; Lan, Yanhua (Journal of thermal analysis and calorimetry, 2024)
To get better insight into the effect of plasticizer 1,5-diazido-3-oxopentane (AZDEGDN) on the decomposition of nitrocellulose (NC) binders, thermogravimetric and reactive forcefield (ReaxFF) simulation was conducted. The decomposition process of NC and NC/AZDEGDN was simulated at different temperatures (1000–3500 K), as well as the reaction path, main products, and decomposition mechanism. The main decomposition products of NC/AZDEGDN by ReaxFF were N 2 , H 2 , NH 3 , H 2 O, CO 2 , and NO 2 , and the main generation pathways were summarized and verified by the radial distribution function. The addition of AZDEGDN decreased the activation energy of NC and accelerated the decomposition of NC. Some molecules and fragments decomposed from AZDEGDN reacted with the intermediates of NC molecular chains and promoted the decomposition of NC. Meanwhile, NO 2 decomposed from NC acted on AZDEGDN molecules to accelerate the decomposition of AZDEGDN. This study provides atomic insights into the decomposition process of NC/AZDEGDN, which may be helpful for further research on the reaction mechanism of energetic fuels.